A report on the practice in industry in fish preservation course - Arnedo, Clotilde J. (College of Fisheries, University of the Philippines, 1958)
Fish, which is second most important food next to rice in the Philippines should be given much attention than any other food. Because of its importance in the Filipino diet, the author studies the various preservation and methods of preparation of this food.